PA.04 Handedness and dementia. Issue 8 (7th July 2011) - El-Nimr, George; Salib, Emad
Abstract : Aims: To explore the possible relationship between handedness and dementia. Methods: A literature review (PsycInfo & MEDLINE). No data limits to the search was applied. Results: Approximately 10 relevant studies identified. Benjamin Seltzer et al ; 1984 reported a higher prevalence of left handedness in early onset dementia. Drexler et al ; 1984 found no significant difference. In 1986 Leon et al found a reduced frequency of left handedness in AD. The possibility that left handers are over represented and die before being diagnosis was raised. Naugle et al ; 1987 found that left handers were more impaired (not statistically significant). In 1998, Raiha et al suggested that there was a reduced risk of AD in ambidextrousness or left handedness. Doodi et al ; 1999 indicated that left handed AD patients had a younger age of onset but lower estimated rates of clinical cognitive decline. There were disproportionately fewer left handers with AD. Parry et al ; 2001 studied the relevance of brain atrophy site. Van Der Elst et al ; 2008 failed to support that left handers are more cognitively impaired. Conclusions: Further work is required to determine potential clinical correlates in relation to handedness & dementia.